Computer architecture : an embedded approach - McLoughlin, Ian (Engineer). (Singapore : McGraw-Hill Education (Asia), 2011)
Presents the subject in a readable and interesting format that provides the background and places emphasis on the increasingly important embedded systems that we all rely upon for our day-to-day living. This book addresses the needs of industry, and interlinks with neighbouring electronics, computer engineering within a typical curriculum.
Includes index.
Keywords: Embedded computer systems; Computer architecture; Computer organization